Magnetoelectronic and optical properties of nonuniform graphene nanoribbons. (November 2016) - Chung, Hsien-Ching; Lin, Yu-Tsung; Lin, Shih-Yang; Ho, Ching-Hong; Chang, Cheng-Peng; Lin, Ming-Fa
Abstract: The electronic and optical properties of nonuniform bilayer graphene nanoribbons are worth investigating as they exhibit rich magnetic quantization. Based on our numerical results, their electronic and optical properties strongly depend on the competition between magnetic quantization, lateral confinement, and stacking configuration. The results of our calculations lead to four categories of magneto-electronic energy spectra, namely monolayer-like, bilayer-like, coexistent, and irregular quasi-Landau-level like. Various types of spectra described in this paper are mainly characterized by unusual spatial distributions of wave functions in the system under study. In our paper, we demonstrate that these unusual quantized modes lead to the appearance of such diverse magneto-optical spectra. Moreover, the investigation of the density of states in our model leads to the appearance of many prominent symmetric and weakly asymmetric peaks. The almost well-behaved quasi-Landau levels exhibit high-intensity peaks with specific selection rules, and the distorted energy subbands present numerous low-intensity peaks without any selection rules.